Сравнительный анализ проекций для компьютерной графики - Качанов, Петр Алексеевич; Зуев, Андрей Александрович; Яценко, Константин Николаевич (НТУ "ХПИ", 2014)
В статье приводится обзор проекций применяемых в системах визуализации. Проведен сравнительный анализ прямой перспективы, перцептивной перспективы и проекции Панини. Рассмотрены математические модели проективных преобразований. На основании этого определены основные преимущества и недостатки при создании изображения трехмерной сцены на плоскости. Представлены сведения о пространственном восприятии человеком окружающего мира. Сделаны выводы относительно практического применения рассмотренных проективных преобразований в компьютерной графике, а так же о возможности реализации.

Linear perspective is a good approximation to the format in which the human visual system conveys 3D scene information to the brain. A perspective image represents the spatial relationships of objects in a scene as they appear from a single viewpoint. The widely used rectilinear perspective projection cannot render realistic looking flat views with fields of view much wider than 60 degrees. The article provides an overview of the projections used in visualization systems. The comparison of the linear perspective, perceptual perspective and projections Panini is made. The mathematical model of projective transformations is presented. The main advantages and disadvantages of projections for creation a three-dimensional scene images on the plane is also described. The information about human spatial perception of real world is provided. Conclusions refer to practical application of projective transformations in computer graphics is discussed, as well as the possibility of realization.
Comparative analysis of projections for computer graphics
Keywords: графические системы; прямая перспектива; перцептивная перспектива; проекция Панини; перспектива Раушенбаха; большой угол обзора; linear perspective; perception perspective; Pannini projection; veduta; Rauschenbach